DEVELOPMENT OF STEM-BASED E-MODULES (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) ON CIRCULAR MOTION MATERIAL TO ENHANCE HIGH SCHOOL STUDENTS' CRITICAL THINKING SKILLS - Ledistika, Mahfira; Medriati, Rosane; Setiawan, Iwan (Jurnal Pendidikan Matematika dan IPA, 2024)
This research aims to determine the feasibility of developing a STEM (Science, Technology, Engineering and Mathematics) based e-mdoul on circular motion material to train Bengkulu City High School students' critical thinking skills. This research method uses RD research with the ADDIE type. The instruments used were interviews, observations and needs analysis questionnaires. The results obtained were 81.07% with the category of strongly agreeing with the development of e-modules. The design of e-module learning media will be developed according to what has been prepared. At the development stage, the instrument used was an expert validation sheet with an average percentage of 87.42% categorized as very suitable for use. At the implementation stage, the instrument used was a student perception questionnaire with a percentage of 83.19% categorized as very good. Thus, it can be concluded that the development of e-module learning media based on STEM (Science, Technology, Engineering, and Mathematics) on circular motion material to train students' critical thinking skills is a very viable product.